Teachers’ Strategies in Addressing Differences in Students’ Learning Abilities in Islamic Boarding Schools - Muhammad Syuaib; Husnul Hilam (Universitas PGRI Sumatera Barat, 2026)
This study aims to examine the strategies used by teachers in addressing differences in students’ learning abilities at Madrasah Diniyah Al-Barokah. The research employs a qualitative descriptive approach, using observation and interview methods. The findings indicate that teachers implement integrated classical learning strategies, form study groups, and use emotional and motivational approaches to adapt to students’ conditions. However, several challenges were identified, such as the limited activeness of Madin teachers, students’ divided focus between formal and diniyah schooling, ineffective evening study time due to non-resident teachers, and physical and mental fatigue resulting from a tight activity schedule. These findings suggest that successful learning is not only determined by the method used, but also by the teacher's sensitivity in understanding the students’ overall condition.